Outcome of laparoscopic adrenalectomy for resection of unilateral noninvasive adrenocortical tumors in 11 cats. Issue 5 (8th April 2017) - Mitchell, Jeffrey W.; Mayhew, Philipp D.; Culp, William T. N.; Brad Case, J.; Singh, Ameet; Fuller, Mark C.; Della Maggiore, Ann
Abstract: Objective: To describe the technique and outcomes of laparoscopic adrenalectomy (LA) in cats with adrenocortical neoplasia. Study design: Retrospective case series. Animals: Eleven client‐owned cats with unilateral adrenal tumors. Methods: Medical records of cats that underwent LA for unilateral functional adrenal tumors at 3 veterinary teaching hospitals were reviewed. Data collected included signalment, clinical signs, physical examination findings, diagnostic imaging results, preoperative laboratory tests, laparoscopic port placement and techniques, duration of anesthesia and surgery, complications, concomitant procedures, need for conversion to an open celiotomy, histopathological diagnosis, and postoperative survival. Results: Eleven cats were included, 5 with right‐sided and 6 with left‐sided tumors. Tumors were aldosterone‐secreting (n = 8), progesterone‐secreting (n = 2), or testosterone‐secreting (n = 1). Adrenalectomy was successfully performed in all 11 cats although 4 cases required conversion to an open celiotomy, due to poor visualization (n = 2), close adherence of the tumor to the caudal vena cava (n = 1), and inability to maintain adequate pneumoperitoneum (n = 1). Ten of the 11 cats were discharged from the hospital, with a median survival time of 803 days (range 467‐1123 days). One cat died from severe pancreatitis and cardiogenic pulmonary edema. Conclusion: Adrenalectomy can be performed in cats via laparoscopy but is technically challenging, and associated with a relatively high conversion rate (36%).